Effects of low concentrations of Regorafenib and Sorafenib on human HCC cell AFP, migration, invasion, and growth in vitro12. Issue 6 (25th February 2013) - Carr, Brian I.; D'Alessandro, Rosalba; Refolo, Maria G.; Iacovazzi, Palma A.; Lippolis, Catia; Messa, Caterina; Cavallini, Aldo; Correale, Mario; Di Carlo, Antonio
Abstract Sorafenib was shown in clinical trial to enhance survival in hepatocellular carcinoma (HCC) patients, but with minimal tumor shrinkage. To correlate several indices of HCC growth at various drug concentrations, HCC cells were grown in various low concentrations of two multikinase inhibitors, Regorafenib (Stivarga) and Sorafenib (Nexavar) and their effects were examined on alpha‐fetoprotein (AFP), cell growth, migration, and invasion. In two AFP positive human HCC cell lines, AFP was inhibited at 0.1–1 µM drug concentrations. Cell migration and invasion were also inhibited at similar low drug concentrations. However, 10‐fold higher drug concentrations were required to inhibit cell growth in both AFP positive and negative cells. To investigate this concentration discrepancy of effects, cells were then grown for prolonged times and sub‐cultured in low drug concentrations and then their growth was re‐tested. The growth in these drug‐exposed cells was found to be slower than cells without prior drug exposure and they were also more sensitive to subsequent drug challenge. Evidence was also found for changes in cell signaling pathways in these slow‐growth cells. Low multikinase inhibitor concentrations thus modulate several aspects of HCC cell biology. J. Cell. Physiol. 228: 1344–1350, 2013. © 2012 Wiley Periodicals, Inc.